Historical Study of Philosophy and Ancient Greek Science: Pre-Socratics and Classical Greece - M. Hasan Ishfi; Salminawati; Ahmad Ardhi Mauluddin Sitorus; M. Imam Nawawi Rangkuti (al-Afkar, Journal For Islamic Studies, 2026)
This study explores the development of philosophy and science in Ancient Greece through a historical approach, highlighting the contributions of philosophers such as Thales, Pythagoras, Plato, and Aristotle in shaping the foundations of rational thought and scientific methodology. The research identifies how Greek philosophy laid the groundwork for scientific traditions by integrating metaphysical speculation with empirical observation. Furthermore, it examines the interaction between philosophical thought and scientific inquiry in fields such as cosmology, mathematics, and biology, which significantly influenced the progress of modern science. Employing a library research method, this study analyzes classical sources and modern literature to reveal how Ancient Greek philosophy and science became a critical foundation for the intellectual evolution of human civilization. The findings demonstrate the relevance of Ancient Greek thought in the context of contemporary knowledge development, particularly in strengthening rational and interdisciplinary approaches across various disciplines.